2022
DOI: 10.1021/acs.jmedchem.2c00256
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Design, Optimization, and Development of [18F]LU13: A Novel Radioligand for Cannabinoid Receptor Type 2 Imaging in the Brain with PET

Abstract: The cannabinoid receptor type 2 (CB2R) is an attractive target for the diagnosis and therapy of neurodegenerative diseases and cancer. In this study, we aimed at the development of a novel 18F-labeled radioligand starting from the structure of the known naphthyrid-2-one CB2R ligands. Compound 28 (LU13) was identified with the highest binding affinity and selectivity versus CB1R (CB2RK i = 0.6 nM; CB1RK i/CB2RK i > 1000) and was selected for radiolabeling with fluorine-18 and biological characterization. The ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 60 publications
(143 reference statements)
0
19
0
Order By: Relevance
“…Several CB 2 R ligands have been developed and evaluated (Ni et al, 2019b), including [ 11 C]NE40 (Vandeputte et al, 2012), [ 11 C]A-836339 (MDTC) (Pottier et al, 2017;Du et al, 2022), [ 18 F]MA3 (Attili et al, 2019), [ 18 F]FC0324 (Caillé et al, 2017), [ 18 F]JHU94620 (Moldovan et al, 2016), [ 18 F]LU13 (Gündel et al, 2022), [ 18 F]DM102 (Modemann et al, 2022), [ 18 F]CRA13 (Hassan et al, 2020), [ 11 C]RS-016 (Meletta et al, 2017), [ 11 C]RS-028 (Haider et al, 2018), [ 11 C]RSR-056 (Slavik et al, 2015), and [ 18 F]RoSMA-18-d6 (Haider et al, 2020). Thus far, only one in-human in vivo CB 2 R PET using [ 11 C]NE40 (Ahmad et al, 2016) in patients with AD and healthy controls has been reported, showing no group difference.…”
Section: Introductionmentioning
confidence: 99%
“…Several CB 2 R ligands have been developed and evaluated (Ni et al, 2019b), including [ 11 C]NE40 (Vandeputte et al, 2012), [ 11 C]A-836339 (MDTC) (Pottier et al, 2017;Du et al, 2022), [ 18 F]MA3 (Attili et al, 2019), [ 18 F]FC0324 (Caillé et al, 2017), [ 18 F]JHU94620 (Moldovan et al, 2016), [ 18 F]LU13 (Gündel et al, 2022), [ 18 F]DM102 (Modemann et al, 2022), [ 18 F]CRA13 (Hassan et al, 2020), [ 11 C]RS-016 (Meletta et al, 2017), [ 11 C]RS-028 (Haider et al, 2018), [ 11 C]RSR-056 (Slavik et al, 2015), and [ 18 F]RoSMA-18-d6 (Haider et al, 2020). Thus far, only one in-human in vivo CB 2 R PET using [ 11 C]NE40 (Ahmad et al, 2016) in patients with AD and healthy controls has been reported, showing no group difference.…”
Section: Introductionmentioning
confidence: 99%
“…CB 2 R has been shown to be increased and involved in Aβ pathology in 5×FAD [61,31] and J20 mouse models of AD amyloidosis [24] but reduced in the brains of 3×Tg mice (with both amyloid and tau pathology) and aging C57B6 mice [56]. Several CB 2 R ligands have been developed and evaluated [39], including [ 11 C]NE40 [54], [ 11 C]A-836339 (MDTC) [9,42], [ 18 F]MA3 [4], [ 18 F]FC0324 [6], [ 18 F]JHU94620 [35], [ 18 F]LU13 [14], [ 18 F]DM102 [34], [ 18 F]CRA13 [17], [ 11 C]RS-016 [32], [ 11 C]RS-028 [16], [ 11 C]RSR-056 [50] and [ 18 F]RoSMA-18-d6 [15]. Thus far, only one in-human in vivo CB 2 R PET using [ 11 C]NE40 [1] in patients with AD and healthy controls has been reported, showing no group difference.…”
Section: Introductionmentioning
confidence: 99%
“…Novel chelators have been reported to be able to incorporate, with high yields, radiometals such as [ 203 Pb]­Pb 2+ , [ 213 Bi]­Bi 3+ , [ 225 Ac]­Ac 3+ , and [ 90 Y]­Y 3+ in short reaction times and under mild conditions with a broad range of pH values. Metal–ligand complexes have been confirmed by 1 H NMR spectroscopy, X-ray crystallography, potentiometry, and computational studies. Development of novel radiotracers to image central nervous system (CNS) receptors. Radiopharmaceuticals binding opioid σ2 receptors, purinergic P2Y 12 receptors, sphingosine-1-phosphate receptor 1, α7 nicotinic acetylcholine receptors, cannabinoid receptor type 2, and Aβ oligomers and plaques have been studied in rodents and non-human primates, demonstrating their ability to cross the blood–brain barrier and bind to CNS targets. Ligand–target interactions at the atomic level have been predicted by perturbation free-energy calculations, molecular docking, molecular dynamics, and metadynamics simulations. ,, Development of radioligands for cancer imaging and therapy with prolonged half-life in vivo and high tumor-to-background contrast.…”
mentioning
confidence: 99%
“…Development of novel radiochemical reactions or chelators to incorporate diagnostic and therapeutic radionuclides in their chemical structure. 10−14 Papers describing novel methods for radiocyanation of aryl halides for the introduction of [ 11 C]CN into peptides, 15 18 F-trifluoromethylation of unmodified peptides at tryptophan and tyrosine residues, 16 and formation of [ 22 sphingosine-1-phosphate receptor 1, 23 α7 nicotinic acetylcholine receptors, 24 cannabinoid receptor type 2, 25 and Aβ oligomers 26 and plaques 27 have been studied in rodents and non-human primates, demonstrating their ability to cross the blood−brain barrier and bind to CNS targets. Ligand−target interactions at the atomic level have been predicted by perturbation free-energy calculations, molecular docking, molecular dynamics, and metadynamics simulations.…”
mentioning
confidence: 99%
See 1 more Smart Citation